Ο ρόλος των κεφαλαιαγορών στη διαχείριση των ασφαλιστικών κινδύνων ανωτέρας βίας - Νεκτάριος, Μιλτιάδης (SPOUDAI Journal of Economics and Business, 2001)
The primary purpose of this article is to review the current insurance and capital markets conversion trends. This trend is more evident in the area of natural catastrophes, which have exhausted the capacity of insurers and reinsurers to underwrite risk. The finance industry has reacted to this situation by issuing innovative products designed to spread the excess risk among international investors. This has occurred with the launching of insurance derivatives (catastrophe futures and options) as well as catastrophe bonds. We analyze the pros and cons of both types of financial instruments and conclude that the securization of natural catastrophe risks by means of cat bonds is the most promising way for increasing the insurance capacity in the catastrophe line of the global reinsurance market. JEL Classification: G22